Avaliação da rede de atenção em saúde e da farmacoterapia de pacientes internados por Condições Sensíveis a Atenção Primária pelo SUS - Mariana Linhares Pereira (2016)
Background: Brazil is currently expanding Primary Health Care (PHC) with the coexistence of two different models: the traditional model comprising Basic Health Units (BHU) and the Family Health Program (FHP). Assessment of the PHC, as well as comparisons of the two available healthcare models, is necessary to evaluate the quality of services delivered to the population. Do not use drugs for treatment ofAmbulatory Care Sensitive Conditions (ACSC) on the health care system results in unnecessary hospitalizations. Objectives: To compare assessments of Primary Health Care (PHC), as rated by patients hospitalized for ambulatory care-sensitive conditions (ACSC), comprising users and non-users of drugs, treated under the different healthcare models (Family Health Program FHP vs. Basic Health Units BHU). Analyze the profile of patients and factors associated to non-use of drugs for ACSC. Methods: A cross-sectional study was conducted within two public inpatient services, city of Divinópolis, Brazil. Data collection was performed by interview and analysis of medical records between July and October 2011. Brazilian version of the Primary Care Assessment Tool (PCATool) was used to assess PHC performance and a questionnaire was applied to assess drugs use. Descriptive analysis was performedand Primary Healthcare Index (PHCI) calculated. Evaluations by drug users and nonusers were compared using the univariate polytomous logistic regression. Patients who do not use drugs to ACSC were compared to those who use drugs to ACSC using logistic regression. The strength of the associations was estimated by odds ratio (OR). All analysis employed 95% confidence intervals (CI). Results: The PHC rating, as assessed by both groups (drug users and non-users), was around 60% of the maximum score (5 points) with no significant difference between them. A total of 314 inpatients were interviewed, 217 (69.1%) of whom were in use of drugs. Approximately 15.0% of drug users reported problems in acquiring drugs and 85% of drugs werepurchased at community pharmacies. Non-use of drugs for ACSC group (59,7%) is younger and have less comorbidities (p=0.000). Employment and health status were associated with non-use of drugs for ACSC. Conclusions: The health services at the primary health care level did not reflect the attributes of PHC and there was no difference in PHC ratings between drug users and non-users. Poor pharmacy services x within the PHC seems to be offered despite the high prevalence of Chronic Non-Communicable Diseases related to hospitalizations for ACSC.